The risk of COVID-19 transmission in a university setting: Undergraduate students' perceptions - Nofi Susanti; Dewi Yanti; Gusti Anom Pramulia; Putri Marliyanti; Tasya Manik; Moch Thoriq Assegaf Al-Ayubi; Ayu Sajida Da'ad Arini; Tri Bayu Purnama (Social Medicine Publication Group, 2023)
Background: The Covid-19 pandemic that occurred in various parts of the world has caused changes in the order of life. The purpose of this study is to examine students' perceptions regarding the potential transmission of Covid-19 in a university setting. Methods: This study is an online survey study with a cross-sectional design. The population of this study is all students domiciled in Medan, Province of North Sumatra, Indonesia. Next, the sample of respondents stratified according to age, gender, and kind of university. The research employed multivariate analysis (Multiple Logistic Regression). Results: Female students are more inclined to believe that Covid-19 cases can spread through activity (P-Value; 0.044 (<0.05), AOR; 0.916, 95% CI: 0.451-1.860). Most respondents enthusiastically supported establishing health protocols on campus. In comparison to students who are confident about implementing health protocols, those who are unsure about compliance may be three times less prepared to begin activities at the university.